1996
DOI: 10.1073/pnas.93.15.7481
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the catalytic fragment of poly(AD-ribose) polymerase from chicken.

Abstract: The crystal structures of the catalytic frag-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(223 citation statements)
references
References 31 publications
5
215
0
3
Order By: Relevance
“…Depending on the specific PARP involved, one to hundreds of ADP-Rib units can be attached to the target (Kim et al, 2005). PARPs are found in all groups of eukaryotes and are characterized by the catalytic site, a b-a-loop-B-a NAD + fold, also called the PARP signature (Ruf et al, 1996;Oliver et al, 2004). This family has been best characterized in humans, where there are 18 family members with diverse functional domains outside of the PARP signature Schreiber et al, 2006;Hassa and Hottiger, 2008).…”
mentioning
confidence: 99%
“…Depending on the specific PARP involved, one to hundreds of ADP-Rib units can be attached to the target (Kim et al, 2005). PARPs are found in all groups of eukaryotes and are characterized by the catalytic site, a b-a-loop-B-a NAD + fold, also called the PARP signature (Ruf et al, 1996;Oliver et al, 2004). This family has been best characterized in humans, where there are 18 family members with diverse functional domains outside of the PARP signature Schreiber et al, 2006;Hassa and Hottiger, 2008).…”
mentioning
confidence: 99%
“…This homology was rather poor at the amino-acid level. However, three-dimensional modeling revealed that the C-terminal region of PARP-10 folded into a domain similar to the PARP domain of ck-PARP-1 (Ruf et al, 1996) (Figure 3). Together with the demonstration that PARP-10 has PARP activity, this protein represents a previously unknown member of poly(ADP-ribose) polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the human PARP-10 sequence is compatible with the architecture of a PARP domain and the three-dimensional structure of the catalytic domain of PARP-10 was modeled according to this alignment using the coordinates of ck-PARP-1 as template (Ruf et al, 1996) (Figure 3e). Several amino acids in the active center are conserved.…”
Section: The C-terminal Domain Of Parp-10 Possesses Parp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This motif is found in the carboxylic-terminal of AMD of only three human PARP-like proteins: PARP-1, PARP-2, and PARP-3 (Hassa et al, 2006;Krishnakumar and Kraus, 2010). The third domain is the carboxylterminal catalytic domain (CD) that catalyzes three different enzymatic reactions: the attachment of the first ADP-ribose moiety onto an acceptor amino acid (initiation reaction), the addition of further ADP-ribose units onto already existing ones (elongation reaction), and the generation of branching points (branching reaction) (Ruf et al, 1996). It is composed of a PARP signature motif; a highly evolutionally conservative sequence that contains key amino acid residues involve in the formation of both the active site and NAD + acceptor site (Rouleau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%